The investment in property: the factors that influences on the housing price index in Malaysia / Hamim Mohd Arrif - Mohd Arrif, Hamim (2018)
For the past 3 decades the price of house in Malaysia has increasing leap and bound from year 1990s, 2000s and 2010s. This research paper objectives are to comes up with a new insight to other researchers about the relationships between macroeconomics data such as Gross Domestic Products, Income, Inflation and Tax with Housing Price Index Malaysia. This research examines the factors that influences on the housing price index in Malaysia from 1987 to 2016. From the 30 yearly data observations, this research applied several empirical tests such as Descriptive analysis, Multicollinearity, Autocorrelation and Heteroskedasticity to determine the relationships towards housing price index in Malaysia. All these data have been Log firstly to make sure the data is linear and perfectly fit to the data. From the results findings there have collinearity between them and Autocorrelation with Heteroskedasticity have failed to reject null hypothesis. But the F-stat in regression analysis have shown below than 5% level significant. The variables data has have use log except tax because the data is not stationary and high prob-value than 5% level og significance. Lastly, the researcher has achieved their objective research and show the significance the research to other researchers as references to them.